Using Deep Learning to Recognize People by Face and Voice - Silva, Lucas Gomes da; Guedes, Álan L. V.; Colcher, Sérgio (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2019: Anais Estendidos do XXV Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2019.8143, 2019)
There are many ways to build a person identification system and those systems can be used for authentication and security. The latest phones for example, bring fingerprint readers to enhance the user experience. From our perspective on Neural Networkswe determine that Machine Learning is enough to guarantee someone’s identity without the need of any specific sensors other than a camera and a microphone. It is achievable with pictures of their face, sounds of their voice and Deep Learning. This work presents a study to build an application to allow biometric authentication using only multimedia and Deep Learning.